Upaya Meningkatkan Kemampuan Membaca Pada Anak-anak kelas 3 - 6 di SDN 1 Mengesta, Desa Mengesta, Tabanan - Nadi, Clarissa Devina; Kurniawan, I Gede Agus (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2023)
Real Work Lecture (KKN) is a form of community service activity with research content that places students off campus and invites students to think critically so that they are able to help develop potential in society with the help of lecturers in solving solutions. The KKN program implemented at SDN 1 Mengesta, Desa Mengesta, Tabanan is a form of education for students at SDN 1 Mengesta who are not yet fluent in reading in a more enjoyable way so that they are interested in being more active in learning to read. The target of this activity is for students in grades 3 to 6 of SD. This is intended so that SD 1 Mengesta students can read and understand long sentences more fluently so that they have no difficulty when they have to read textbooks or answer questions with long sentences. Elementary school students, especially grades 3 to 6, must be able to read fluently and even understand the contents of the reading so that learning at school is more effective and the knowledge gained is more understandable. The role and full support of parents and teachers at school is also very important because it is one of the factors for a child's success at school, in this case also including the ability to read. ==== Kuliah Kerja Nyata (KKN) merupakan bentuk kegiatan pengabdian kepada masyarakat dengan muatan penelitian yang menempatkan mahasiswa di luar kampus dan mengajak mahasiswa berpikir kritis sehingga mampu membantu mengembangkan potensi di masyarakat dengan bantuan dosen dalam pemecahan solusinya. Program KKN yang dilaksanakan di SDN 1 Mengesta, Desa Mengesta, Tabanan merupakan bentuk edukasi kepada siswa/i SDN 1 Mengesta yang belum lancar membaca dengan cara yang lebih menyenangkan sehingga tertarik untuk lebih giat dalam belajar membaca. Sasaran kegiatan ini adalah untuk siswa/i kelas 3 sampai 6 SD. Hal ini bertujuan agar siswa/i SD 1 Mengesta dapat membaca dan memahami kalimat-kalimat panjang dengan lebih lancar sehingga tidak kesulitan saat harus membaca buku pelajaran atau menjawab soal-soal dengan kalimat yang panjang. Siswa/i Sekolah Dasar, terutama kelas 3 sampai 6 SD, harus sudah dapat lancar membaca bahkan memahami isi bacaan sehingga pembelajaran di sekolah lebih efektif dan pengetahuan yang didapat lebih dimengerti. Peran dan dukungan penuh orang tua serta guru di sekolah juga sangat penting karena menjadi salah satu faktor keberhasilan anak di sekolah, dalam hal ini juga termasuk kemampuan membaca.